Expanded carrier screening in Chinese patients seeking the help of assisted reproductive technology. Issue 9 (23rd June 2020) - Xi, Yanping; Chen, Guangquan; Lei, Caixia; Wu, Junping; Zhang, Shuo; Xiao, Min; Zhang, Wenbi; Zhang, Yueping; Sun, Xiaoxi
Abstract: Background: Expanded carrier screening (ECS) has emerged as an effective approach to identify at‐risk couples (ARCs)—before they initiate attempts at reproduction—who possess a high probability of having a child affected by severe recessive diseases. The objective of this study was to evaluate the clinical utility of ECS in Chinese patients seeking the help of assisted reproductive technology (ART). Methods: An ECS test, which covers 201 genes implicated in 135 recessive (autosomal or X‐linked) diseases, was routinely offered to all ART patients in a single genetics and in vitro fertilization clinic. Additional options for preimplantation or prenatal genetic diagnosis were discussed and offered to all ARCs. All ECS results were aggregated and the clinical decisions of the ARCs were surveyed. Results: A total of 2, 923 ART patients, representing 1, 462 couples, were screened. Overall, 46.73% of the individuals were found to be the carriers for at least 1 of the 135 diseases. Of the tested couples, 2.26% ( n = 33) were identified as ARCs. As of the completion of this study, 21 (63.6%) ARCs have decided to avert an affected pregnancy with the help of preimplantation genetic testing for monogenetic conditions. The cumulative carrier rate of the 187 autosomal recessive genes in the ECS panel for the 2, 836 Han Chinese individuals without a family history was estimated to be 45.91%. The estimated at‐risk couple rate indicates that the screening for only the top 31 genes with gene carrier rates >0.5% would identify more than 94% of the ARCs identified by screening all 187 genes. Conclusion: Our study demonstrates that ESC yields a significant clinical value for ART patients in China. In addition, by estimating the yields of the ECS panel, we identify genes that are appropriate for screening the Han population. Abstract : We launched a pilot population based expanded carrier screening(ECS) for 135 severe recessive Mendelian conditions in Chinese patients seeking the help of assisted reproductive technology (ART). Our study demonstrates that ESC yields a significant clinical value for the ART patients in China. In addition, by estimating the yields of the ECS panel, we identify genes that are appropriate for screening the Han population.